Reputational crisis at a Chilean University, resulting from a post on social media X (Twitter) about the controversial theses in the School of Philosophy and Humanities - Amigo-López, Thierry; Rojas-Gomez, Diana (Frontiers in Education, 2024)
Due to the prominence of social networks since the second decade of the 21st century, online reputation has become an essential aspect for universities. The University of Chile, a public institution, faced a reputational communication crisis at the end of 2022 due to the disclosure on X (formerly Twitter) of two theses that relativized the concept of pedophilia. This situation raised questions about ethical integrity and permissiveness in academic research. This study was designed to understand the impact of these theses on the social perception of the university. A qualitative approach supplemented with descriptive quantitative data was adopted. The research was conducted in two phases. First, comments on X related to the controversy were reviewed in general. Then, links to the comments were compiled and organized into a table. These data were downloaded from the Export Comment platform; from a total of 4680 posts, a sample of 500 comments was selected. Second, the comments were inductively categorized using Atlas.ti23, and their content was analyzed. The results showed high disapproval by X users regarding the content of the theses and the university's communication management. However, this did not directly alter the institutional reputation of the university, although it did influence the perception of the external public towards the professors, affecting the internal environment of the organization. The paper concludes that the comments in X reveal a momentary absence of protocols by the university for the evaluation of academic projects, i.e., this contingency could be protected with an improvement in university management.